Relationship of Knowledge And Attitude of Nurses With Quality Of Nursing Care In RSUD Tarutung - Dawson Hutauruk; Nurlela M. Nababan; Trimey Liria Hutauruk (Science Midwifery, 2021)
Quality service is the hope of all clients who are brought and treated at the hospital, however not all hospitals are able to provide the desired service. This is because quality services can only be provided by health professionals who have good knowledge and abilities, so that patients feel comfortable. Convenience greatly affects the quality of the treatment undertaken. This study uses a cross sectional design. The total population is 35 nurses with a sample of 34 nurses using total sampling. Data analysis using the chi square test with a degree of confidence p <0.05. Based on the results of the chi square test there is a relationship between knowledge and attitudes of nurses with the quality of nursing care in RSUD Tarutung with a significance degree (α) = 0.05 and df = 1, the calculation results are Sig (2-tailed) 0.013 > (α) = 0.005, then Ho is rejected and Ha is accepted. It is recommended for nurses. The results of this study can be used as input to improve the quality of nursing services in providing more services for patients.